A new proof of Ackermann’s formula from control theory - COSTANDIN, Marius; DOBRA, Petru; GAVREA, Bogdan (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
This paper presents a novel proof for the well known Ackermann’s formula, related to pole placement in linear time invariant systems. The proof uses a lemma [3], concerning rank one updates for matrices, often used to efficiently compute the determinants. The proof is given in great detail, but it can be summarised to few lines. Mathematics Subject Classification (2010): 26D10, 46N30.